Topic Finder for Use With The Art of Public Speaking - Stephen E. Lucas (McGraw-Hill Higher Education, 2013)
This publication is a pamphlet with 17 unnumbered pages and 7 pages that are blank except for being labeled as Notes. The pamphlet serves its stated purpose of stimulating the imagination with ideas that will help lead you to a topic of your choosing. As a random sampling, here are the first 10 listings under the alphabet letter O: oats,obesity obscenity, occultism, occupational therapy, oceanography, octopus, Odyssey, offshore drilling, and O Keefe, Georgia.